Exploring the factors that affects Romanian religious tourism: The case of Oradea city - Elena Aurelia Botezat; Ada Mirela Tomescu (UTMS Journal of Economics, 2018)
The purpose of this paper is to contribute to a better understanding of the critical factors responsible for the success of religious tourism in Romania, meaning a sustainable success. In the special case of religious tourism, this seems much easier to accomplish, but in Romania there is a lack of studies to show this. The research outcomes show that the critical/decisive/determinants success factors in religious tourism depends on: the attractiveness of the location, the avoidance of excessive exposure of the elements of the religious offer, the limitation of the commercial activity, and how participants behave. This paper is important, both for the assessment of religious tourism and for the possibility of the tourist destinations sustainable development strategy. The results of this research reveal that decisions should not be taken alone on the basis of a single set of factors, but that they should be taken together, taking into account all the factors involved. Also results indicate a focus on all stakeholders, highlighting current identified trends. The work is focused on how the experiences of religious tourism are evaluated, and it is followed by some conclusions and limitations. This study being a preliminary work, in the future, the research should address the relative importance of these factors for different segments of the religious tourism consumers.
Keywords: L83; Z12; 330; critical success factors; assessment; sustainable development